Mass Media in a Changing World - George Rodman (Mc Graw Hill, 2006)
2 eksemplar @2 CD, Besar file CD 1: 697 MB, CD 2: 538 MB, Durasi CD 1 : 02;03;21 CD 2 : 01;34;47, CD 1 berisi : Media Tours Videos, NBC Video Clips, Online Learning center; CD 2 berisi : Mulitiple Choice Quiz, True or False Quiz, Essay Quiz. Judul dalam kemasan.